Variables that affect the purchase intention of Peruvian gastronomy - Azambuja, Gina Pipoli de (European Journal of Economics and Business Studies, 2017)
The purpose of the research is analyze the association of the purchase intention of Peruvian gastronomy with the following set of variables: the country image of Peru, the gastronomy s product image, the familiarity with Peru, and the gastronomy s product familiarity. Such association has not been studied for country familiarity variable, and for Peruvian gastronomy. A qualitative method to compile the primary information and the survey technique was used. Additionally, a questionnaire of closed questions was applied to undergraduate and graduate students in two selected samples that correspond to the consumers of two countries with different levels of familiarity with Peru: United States whose level of familiarity is high and France whose level of familiarity is low. It was concluded that there is a positive relation between the intent to purchase of Peruvian gastronomy with the country image of Peru, the gastronomy s product image, the familiarity with Peru, and the gastronomy s product familiarity. In addition, the country image of Peru is statistically significant associated with purchase intention of Peruvian gastronomy for the case of foreign consumers with high and low familiarity with Peru.